Improving grouper production through effective fish health management - Mohd Ikhsan, Natrah Fatin; Shamsudin, Mariana Nor; Md. Noor, Noorashikin; Khairuddin, Nurul Aiman Nafisah; Mohd Daud, Hassan; Md. Yusoff, Fatimah; Md Yasin, Ina Salwany; Abd Karim, Murni Marlina; Nazarudin, Muhammad Farhan (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
A collaboration between UPM and RE Millenium Sdn. Bhd. has been initiated to improve the tiger grouper E. fuscoguttatus production. For that purpose, several activities have been carried out which include field visits by university collaborators and graduate interns, discussions on different future projects with the industrial partner and workshop to train the RE Millenium staffs particularly on the live feed production and health management. Meanwhile, further research to improve the larval and juvenile production of grouper are on-going. The research involved the use of beneficial microbes through synbiotic approach and bioremediation properties.